Change in land use in areas of great flood hazard in Slovenia between years 2000 and 2016 - Balek, Dejvid (Journal for Geography, 2017)
The article presents trends in transformation of land use in areas of great flood hazard in Slovenia between years 2000 and 2016. Focuse is mainly on probe areas Dolinsko, Krško-Brežice Field and Ljubljana Marshes. We analysed the land use in probe areas and in seven Slovenian municipalities with the largest combined surface of areas of great flood hazard for both years of this study. Our focuse was mainly on inappropriate land use in the areas of great flood hazard in Slovenia.